Anti-malarial activity in a Chinese herbal supplement containing Inonotus obliquus and Panax notoginseng. (April 2022) - Endo, Takuro; Nakagomi, Yuki; Kawaguchi, Eri; Hayakawa, Eri Saki H.; Vu, Hoai Nam; Takemae, Hitoshi; Shinohara, Yuta; Yang, Da; Usui, Tatsuya; Mizutani, Tetsuya; Nakao, Yoichi; Furuya, Tetsuya
Abstract: Plasmodium falciparum, the most virulent human malaria parasite, causes serious diseases among the infected patients in the world and is particularly important in African regions. Although artemisinin combination therapy is recommended by the WHO for treatment of P. falciparum -malaria, the emergence of artemisinin-resistant parasites has become a serious issue which underscores the importance of sustained efforts to obtain novel chemotherapeutic agents against malaria. As a part of such efforts, thirty-nine herbal extracts from traditional Chinese medicine (TCM) were assayed for their anti-malarial activity using 3D7 strain of P. falciparum. Three herbal supplements appeared to possess higher specific anti-malarial activity than the others. One of them (D3) was separated by two sequential fractionations with reverse-phase (the first step) and normal-phase (the second step) liquid chromatography, in which some fractions resulted in higher specific activities than those of D3 or the previous fractions. Cell toxicity assay was performed with the fractions of the first fractionation and demonstrated no obvious cell toxicity. These results suggest that structure determination of the major compound for the anti-malarial activity in D3 may help the development of more potent chemicals in the future.